Effect of Different Factors on the Leakage Current Behavior of Silicon Photovoltaic Modules at High Voltage Stress - Islam, Mohammad Aminul; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (Institute of Electrical and Electronics Engineers, 2018)
Leakage current is one of the determinants of potential-induced degradation (PID) of the photovoltaic (PV) module. Effects of different parameters such as module surface temperature, surface wetting, salt and dust accumulation, and aging condition on high-voltage-stress (HVS) leakage current of the crystalline PV module are investigated in the laboratory. In this research, a novel notion on HVS-leakage-current-modulating parameters has been introduced, which is useful to assess the HVS degradation at different climates. The leakage current increases moderately with the increase of module surface temperature, and it increases drastically during the surface wetting condition. The leakage current under 1000-V stress is 5.04, 5.82, and 35.55 μA/m2 at 25 °C (50% relative humidity), 60 °C (8% relative humidity), and 45 °C (wet) conditions, respectively. The presence of salt also increases the leakage current almost linearly. A slight amount of dust (2 g/m2) on the module surface was found to trigger the wet leakage current to a considerable limit. Tiny dust particles have a capability to attach with some ionic compounds, where Na ions are dominant from the coastal area that prompts the leakage current of the PV module. Long-term field operation known as aging of the PV module reduces the electrical resistance of ethylene vinyl acetate; consequently, the leakage current, as well as PID, increases significantly.